Integration of Google Drive and Google Forms as Digital Media in Teaching Maharah Istima’ to Madrasah Aliyah Students - Rahmawati, Bintang Lutfi (Abjadia : International Journal of Education, 2025)
This study aims to examine the effectiveness of digitizing learning media through the Google Drive and Google Form platforms in improving students' listening skills (maharah istima') in Arabic language learning. Using a quasi-experiment method with a one-group pretest-posttest design, this study involved students who actively used digital platforms as learning media. The results showed a significant increase in the average score from pretest (68) to posttest (82), as well as a positive response from learners to the use of digital media, where more than 85% of students felt more enthusiastic, understood the material better, and wanted to continue using digital media. The Google Drive platform allowed flexible access to audio materials, while Google Forms made it easier to evaluate and analyze learning outcomes. The findings show that the integration of digital technology positively contributes to the improvement of students' maharah istima' skills, learning motivation and independence, as well as being an adaptive solution to the challenges of learning in the digital era.